Investigation of Parametric Resonance in Roll for Container Carrier Ships - Ghamari, Isar; Faltinsen, Odd Magnus; Greco, Marilena (Volume 11: Prof. Robert F. Beck Honoring Symposium on Marine Hydrodynamics, 2015)
Parametric roll resonance is of concern for container and fishing vessels, especially in head-sea waves. Here this phenomenon is investigated with a numerical method based on potential-flow theory with viscous corrections for the roll damping. The seakeeping problem is handled by considering a strip theory and assuming a 5-DOF system. Nonlinearities are accounted for in the Froude-Krylov and hydrostatic loads. The solver has been validated against experiments on a C11 class container carrier ship in terms of parametric resonance occurrence and features for different ship forward speeds and headings, wavelengths, wave amplitudes and wave headings. The overall agreement is good but there are some discrepancies. For instance, the simulations show capsizing in some cases while it does not happen in the experiments. The results from present method can be used to generate 2D and 3D polar diagrams identifying the zones with parametric roll occurrence, and are very handy for masters aboard ships. This type of information is valuable at design stage and can be used aboard vessels for a safer voyage. publishedVersion (c) 2015 by ASME